My Shakespeare a director's journey through the first folio - Doran, Greg (Methuen Drama, a trademark of Bloomsbury Publishing Plc, 2023)
This book charts the personal and professional journey of Greg Doran, Artistic Director of the Royal Shakespeare Company from 2012 until 2022 and "one of the great Shakespearians of his generation" (Sunday Times). During his illustrious career, Doran has directed or produced all of the plays within Shakespeare's First Folio -- a milestone reached in the same year that the world celebrates the 400th anniversary of its original publication. Each chapter looks at a different play, considering the choices made and weaving in both autobiographical detail and background on the RSC, as well as giving insights into key collaborations, including those with actors such as Judi Dench, David Tennant, Harriet Walter, Patrick Stewart, Simon Russell Beale, Paterson Joseph and Doran's husband, the late Antony Sher, as well as seminal practitioners such as Cicely Berry, John Barton and Terry Hands. Through Doran's account of this extraordinary journey, we see how Henry VIII, initially regarded as a poisoned chalice, became his lucky break; how the tragedy of 9/11 unfolded during a matinee of King John and how the language of the play went some way in helping to articulate the unfathomable; how a RSC supporter bequeathed their skull to the company to be used as Yorick in Hamlet; how meeting Nelson Mandela inspired the production of Julius Caesar; how Falstaff was introduced to China for the very first time; and how arachnophobia informed the production of Macbeth. This book uniquely captures the excitement, energy, surprises, joys and agonies of working on these greatest of plays; sheds new light on these plays through Doran's own research and discoveries made in the rehearsal room; and gives unprecedented access into the craft, life and loves of this exceptional director"--Provided by publisher.